(3JMaI GdabjQ Edi UGMH GdSQjQs - (3eMeO Hf EHQGgje GdEjLj,J (B840 (3g` s ((3HjQYdi GdMGaX s)
(3ChdgG (B:s
(3GdMeO ddg GdPi habfG GdSdhc efGgL GdMb hGdUOb s
(3BNQgG (B:s
(3hfSCd Gddg SHMGfg hJYGdj Cf jfHgfG Yf SfI GdZGadjf, hjSdc HfG SfI GdZGadjf s
(3gh cJGH ai GdJGQjN GdYGes
(3GdeDda cGf MjkG SfI (B800(3g` ceG aj oeYLe GdeDdajf (B193/8s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B193s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B255 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B99 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs